WAQF ACCOUNTABILITY FROM THE STAKEHOLDER SALIENCE THEORY: A CASE STUDY - Ihsan, Hidayatul; Sulaiman, Maliah; Mohd Alwi, Norhayati; Akhyar Adnan, Muhammad (Bank Indonesia, 2016)
This study aims to address the issue of accountability in a waqf institution. Specifically, the focus of this study is to shed more light on how the mutawalli (waqf trustee) discharges accountability in managing waqf. In so doing, an interpretive case study in one Indonesian waqf institution, that is, Dompet Dhuafa (DD), was undertaken. The data were obtained through semi-structured interviews. Other sources of data collection techniques employed along with the interviews include observations and document reviews. Furthermore, this study uses the accountability mechanisms as the conceptual lens. The accountability mechanisms consist of disclosure statements and reports, performance assessment, participation, self-regulation and social auditing. In addition to the accountability mechanims, the stakeholder salience theory is also used to understand how the mutawalli shows accountability to multiple stakeholders. The findings of this study reveal that although DD recognizes the salient nature of its stakeholders, it does not prevent the mutawalli from showing accountability to all stakeholders. The mutawalli is of the view that accountability is not limited to accounting and reporting. Moreover, the mutawalli believes that showing accountability to different groups of stakeholder requires different mechanisms of accountability. As such, this study concludes that DD’s commitment to accountability is proven through its effort to deal with stakeholder salience.